Biphasic synovial sarcomas of the liver: a case report and literature review - Defeng Liang; Lingyu Meng; Shanshan Wang; Dan Yi; Yahui Liu (Diagnostic Pathology, 2022)
Abstract Background Synovial sarcoma is a soft tissue sarcoma of temporarily unknown histologic origin with the ability for biphasic differentiation, occurring mostly in the vicinity of large joints of the extremities. Synovial sarcoma that originates in the liver is extremely rare. Only 7 cases have been reported in the domestic and international literature. Case presentation We report an 11-year-old female patient who underwent partial hepatectomy for a liver mass. Microscopically, she was diagnosed with hepatic biphasic synovial sarcoma. Cytogenetic examination revealed the fusion gene SS18-SSX1 (+), which confirmed the diagnosis. Conclusion Synovial sarcoma of the liver is a rare malignancy that is difficult to diagnose. Confirmation of diagnosis is based on histopathological assessment combined with immunohistochemical staining and, if necessary, cytogenetic aids.